2011
DOI: 10.1111/j.1600-0897.2011.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Circulating CD4+ CD25+ Foxp3+ T Regulatory Cell Levels Predict Miscarriage Risk in Newly Pregnant Women with a History of Failure

Abstract: PROBLEM  The purpose of this study was to determine whether quantification of peripheral blood Treg cell levels could be used as an indicator of miscarriage risk in newly pregnant women with a history of immunologic reproductive failure. METHOD OF STUDY  Fifty-four pregnant women with a history of immunologic infertility and/or pregnancy loss were retrospectively evaluated (mean age: 36.7 ± 4.9 years, 2.8 ± 2.5 previous miscarriages; 1.5 ± 1.9 previous IVF failures). Twenty-three of these women experienced ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 41 publications
2
62
0
3
Order By: Relevance
“…In 2004, Aluvihare et al and our group first reported that Treg cells might mediate maternal tolerance to the fetus in mice and humans (Aluvihare et al, 2004;Sasaki et al, 2004). Since then, many lines of evidence supporting the importance of Treg cells in the implantation period and the early pregnancy period have been presented, with more detailed characterization of Treg cells in mice (Zenclussen et al, 2005(Zenclussen et al, , 2006DarrasseJèze et al, 2006;Kallikourdis et al, 2007;Robertson et al, 2009;Shima et al, 2010;Kahn and Baltimore, 2010;Guerin et al, 2011;Rowe et al, 2011Rowe et al, , 2012Samstein et al, 2012;Yin et al, 2012) and in humans (Tilburgs et al, 2008(Tilburgs et al, , 2009Sasaki et al, 2007;Yang et al, 2008;Jin et al, 2009;Mei et al, 2010;Wang et al, 2010Wang et al, , 2011Winger and Reed, 2011;Lee et al, 2011;Steinborn et al, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…In 2004, Aluvihare et al and our group first reported that Treg cells might mediate maternal tolerance to the fetus in mice and humans (Aluvihare et al, 2004;Sasaki et al, 2004). Since then, many lines of evidence supporting the importance of Treg cells in the implantation period and the early pregnancy period have been presented, with more detailed characterization of Treg cells in mice (Zenclussen et al, 2005(Zenclussen et al, , 2006DarrasseJèze et al, 2006;Kallikourdis et al, 2007;Robertson et al, 2009;Shima et al, 2010;Kahn and Baltimore, 2010;Guerin et al, 2011;Rowe et al, 2011Rowe et al, , 2012Samstein et al, 2012;Yin et al, 2012) and in humans (Tilburgs et al, 2008(Tilburgs et al, , 2009Sasaki et al, 2007;Yang et al, 2008;Jin et al, 2009;Mei et al, 2010;Wang et al, 2010Wang et al, , 2011Winger and Reed, 2011;Lee et al, 2011;Steinborn et al, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…Recently, it was proposed that low levels of CD25 + FOXP3 + cells could be used to predict miscarriage in women with a history of previous failures. 109 Taken together, data indicate that defects in numbers or function of Treg cells may be involved in the development of RM.…”
Section: Treg Cells In the Complications Of Pregnancymentioning
confidence: 99%
“…Cette chute des cellules Treg pourrait être impliquée dans le déclenchement du travail puisque qu'elle est moins importante en cas de césarienne programmée [68]. Certains avortements à répétition humains sont associés à des déficits en cellules Treg déciduaux [69] ou circulants [70].…”
Section: Trophoblaste Et Cellules T Régulatrices (Cellules Treg)unclassified